Leitor e leitura : um estudo sobre as práticas de leitura de alunos do nono ano de escolaridade de uma escola da rede estadual de São Gonçalo/RJ - Kirk, Edilaine Vilar (2009)
We investigated the practices of read trying to dimension the importance of the read in the social, school and individual environment, looking for consider the material support of read and know and analyze the catalogues and practices of read beginning in the school and family formation. Tracing the student s history of read and their parents, we tried to identify the way that the act of read frequently (or not), the text s support possession (or not), the familiar influence and others factors not presumed initially can interfere (or not) in the relationship between student and read. This research were achieved based in Bakhtin s studies that privilege the language s social nature , like Bourdieu and Lahire that concentrate their studies in the relationship between social structures and the constitution of the subjectivity. With the intention of join together the founded data with the studies realized in the latest years, about the read, we choused for establish an dialogue with researches realized about the theme; we turned to a bibliography research that includes information about the Anped s meet, some articles, thesis and dissertations mapped by CAPES and scientific articles published in qualified magazines and authors that can complete the research yet.